(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
In today’s interconnected world, data security has become a top concern for individuals, businesses, and governments. With the exponential growth of digital data and the rise of cyber threats, protecting sensitive data has never been more important. Data breaches, identity theft and ransomware attacks are on the rise, highlighting the need for strong security measures. The consequences of a data breach can be devastating, leading to financial losses, reputational damage and legal ramifications. As a result, organizations must prioritize protecting their data assets in order to maintain trust with customers and stakeholders. By implementing comprehensive security protocols, including encryption, access controls, and regular security audits, organizations can reduce the risk of data breaches and protect their valuable information. In the era of digital transformation, data security is not only best practice, but also the need to ensure the integrity and confidentiality of sensitive data